Strengthening Religious Moderation Based on Cultural Communication in Facing Socio-Religious Issues in Multicultural Communities - Nur Ahmad; Farandika Nanda Pratama; Miftakhul Jannah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme)
This study explores the strengthening of religious moderation through cultural communication in addressing socio-religious issues within multicultural communities. Employing a qualitative approach with library research methods, this study analyzes primary sources such as scholarly books, accredited national and international journals, and relevant policy documents. Data were collected through documentation and analyzed using content analysis techniques to identify patterns related to moderation, communication, and 21st-century skills. The findings reveal that religious moderation cannot be conveyed solely through normative doctrines; it must be contextualized through inclusive cultural communication that respects diversity. Core moderation values such as tawassuth, tasamuh, tawazun, i’tidal, and musawah are more effectively internalized when embedded in local communication practices. Additionally, the integration of 21st-century skills such as critical thinking, communication, collaboration, and creativity contributes significantly to cultivating tolerant individuals capable of navigating the complexities of contemporary social and religious life. This study provides a conceptual contribution by linking cultural communication with the mastery of 21st-century skills, a connection not thoroughly addressed in previous research. The implications emphasize the role of educational institutions, religious leaders, and media in fostering a moderate, inclusive society. Ultimately, religious moderation must be actualized through everyday practices supported by strategic communication and relevant competencies for navigating pluralistic realities.